5 Pen PC Technology: A Portable Computer - Shweta M. Chaple; Krishna T. Madrewar (International Journal of Radio Frequency Innovations, 2024)
A recent advancement in the field of pen computing is known as “5 pen technology.” Computers have a considerably bigger impact on our lives than most of us may realize. Becoming proficient in computer software has become essential for most occupations. The ENIAC, the first computer ever created in 1943, had more power than several hundred contemporary PCs and was the size of a big room. Integrated circuit-based modern computers are compact enough to fit into portable electronics. Table computers are among the smallest computers available right now; the most well-known model is the I Pad, although even that device is only 9. 1 inch and weighs roughly 700 grammes. However, picture owning a computer that can tuck into your pencil case. The P-ISM, or Pen-style Personal Networking Gadget bundle, is a collection of five pens, each serving a unique function and operating in tandem to generate a virtual computing environment. This is merely a prototype that NEC Corporation is currently developing. The ITU telecom Word presentation took place in Geneva in 2003, and it featured a proposed P-ISM prototype that cost $30,000. The prototype was created by the Tokyo-based NEC Corporation.
Keywords: 360 degrees camera; Portable Workstation; Ubiquitous computing; Wireless Bluetooth Technology